Budding systems of ’Valência’ orange on ’Rangpur’ lime, and protection of file stocks with plastic bags - Dornelles, Ana Lúcia Cunha; Koller, Otto Carlos; Manica, Ivo (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was performed at the Guaíba, RS, Brazil. It compared two budding systems of 'Valencia' orange (Citrus sinensis (L.) Osbeck) over 'Rangpur' lime (Citrus limonia Osbeck): table budding by "hanging bud' and nursery budding by inverted “T", and four protection periods of the stocks with plastic bags (30, 45, 60 and 75 days after transplanting from seedbed). There was no difference between the table budding and nursery budding systems. The stock protection, for 30 to 45 days with plastic bags increased the bud setting and improved the budshoot development.